Penatalaksanaan Holistik Pada Ibu Hamil Dengan Kurang Energi Kronis (KEK) Melalui Pendekatan Kedokteran Keluarga - Marissa Herani Praja; Aila Karyus (CV. Jasa Sukses Abadi, 2020)
Chronic energy deficiency (CED) is a state of chronic energy and protein intake shortages that persists (chronic) resulting in health problems for the mother and fetus. Implementation of evidence based medicine based family doctor services by identifying risk factors, clinical problems, and managing patients holistically with a patient centered approach, family approached, and community oriented. Primary data obtained through history taking, physical examination and home visits, psychosocial and environmental data. Assessment is based on a holistic diagnosis from the beginning, process, and end of the study quantitatively and qualitatively. The patient, a 25-year-old woman pregnant with her fourth child, 24 weeks gestasional age with chronic energy deficiency, has concerns about growth, development and the fetus and herself. Complaints feel weak, no appetite at the beginning of the trimester, and difficulty to gain weight. The patient also has a history of miscarriage twice. The risk factor obtained is the lack of adequate nutritional balance in patients. In the process of behavior change, Mrs. T has reached the trial stage. The process of behavior change for a balanced nutritional diet, addition of food portions, routine vitamin intake and Supplementary feeding (SF)-mild physical exercise is seen after the patient is given an intervention.